2012
DOI: 10.1159/000338510
|View full text |Cite
|
Sign up to set email alerts
|

Cockroach Allergen per a 7 Down-Regulates Expression of Toll-Like Receptor 9 and IL-12 Release from P815 Cells Through PI3K and MAPK Signaling Pathways

Abstract: Background: As a major source of indoor allergens, cockroach causes perennial rhinitis and asthma. Recently, cockroach feces were reported to contain TLR2 agonist, which could directly activate neutrophils to release cytokines. CpG oligodeoxynucleotide (ODN), a Toll-like receptor (TLR)9 activator was also found to induce proinflammatory cytokine release from mast cells. However, influence of specific cockroach allergen on Th1 cytokine release and expression of TLR9 in mast cells remains uninvestigated. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 35 publications
1
12
0
1
Order By: Relevance
“…wnt ligand WNT5A. p38 phosphorylation and p65/NFκB phosphorylation were also investigated as mediators of TLR signaling (Brown et al, 2011;DelaRosa and Lombardo, 2010;Yang et al, 2012). We found that p38 and p65 phosphorylation occurred after 30 min treatment with rhSAA1 in 3 different hMSC donors.…”
Section: Saa Expression Is Associated With In Vitro Aging Of Hmscmentioning
confidence: 86%
“…wnt ligand WNT5A. p38 phosphorylation and p65/NFκB phosphorylation were also investigated as mediators of TLR signaling (Brown et al, 2011;DelaRosa and Lombardo, 2010;Yang et al, 2012). We found that p38 and p65 phosphorylation occurred after 30 min treatment with rhSAA1 in 3 different hMSC donors.…”
Section: Saa Expression Is Associated With In Vitro Aging Of Hmscmentioning
confidence: 86%
“…TLR3, 7, 8 and 9 are intracellular TLRs and their signaling cascade is depicted in figure 1 [19,23,41,42]. Viral infections, especially with rhinovirus, account for the most common causes of asthma exacerbation in children and cause more severe forms of wheezing episodes in allergic subjects [83].…”
Section: Intracellular Tlrsmentioning
confidence: 99%
“…This shows that not all infections and not all farming environments are protective. Interestingly, many triggers of asthma, such as environmental allergens and air pollutants, act in part via modulation in PRR expression and function [17,18,19,20]. Furthermore, the generation of reactive oxygen species is increased in asthma and AR, with oxidative stress being one factor that causes exacerbation of disease.…”
Section: Introductionmentioning
confidence: 99%
“…They are generally complex heteropolymers, in contrast to the storage homopolymers that made up glycogen and amylose. More recently, intravenous and subcutaneous immunoglobulin preparations contain carbohydrate-specific IgG antibodies to microbial antigens, tumor-associated carbohydrate antigens, and host glycans (51), implicating the importance of these modifying macromolecules in human health and disease. Furthermore, polysaccharides, widely concerned as bioactive macromolecules in recent centuries, have been proved to benefit the intestinal health.…”
Section: Introductionmentioning
confidence: 99%